Organizational Culture, Transformational Leadership, Job Satisfaction Influence on Employee Engagement in Millennial Generation - Suryaningrum, Dian Kristiana; Tunas, Billy; Yohana, Corry (Archives of Business Research, 2019)
This paper investigates whether there is a direct effect of organizational culture, transformational leadership, and job satisfaction on employee engagement of millennial generation. The analysis of this study uses path analysis to test the hypothesis and takes 399 simple random sampling of millennial employees. The research finds that sales who are all millennial generation in 2017, fall into the 15% engaged category, 72% in the not engaged category and 13% in the actively engaged category. The low level of sales fall in the engaged category causes high turnover. This study successfully revealed novelty, and that is making modeling that integrates several variables studied including organizational culture, transformational leadership, job satisfaction and employee engagement in the millennial generation in which transformational leadership must become the management focus area priority to increase the sales’ engagement. It is required an effort from top leaders to create a strong organizational culture that will lead to increase job satisfaction and higher employee engagement.